IMPROVE CUSTOMER SATISFACTION THROUGH DEMO OPEN KITCHEN IN SOCIAL MEDIA - Prasetya Tri Mahendra; Muhammad Bawono; Ulfa Aziza Umairoh (Value : Jurnal Manajemen dan Akuntansi, 2021)
The purpose of this study was to determine and explain the use of demo open kitchen to consumer satisfaction through social media at HK Food Service Company, Nganjuk. This type of research uses quantitative research methods with a causal associative research design. In determining the sample, researchers used 73 consumers. Analysis of the data used by using the validity test, reliability and classical assumption test. Hypothesis testing is done by performing t statistical tests, with data collection techniques in the form of online questionnaires. Hypothesis testing by doing t statistical test with the results of the study concluded that the demo open kitchen has a partial effect on customer satisfaction, as evidenced by the acquisition of the t value is greater than t table with a significance of less than 0.05. Keywords : Demo Open Kitchen, social media, consumer satisfaction